(untitled) (American Journal of Islam and Society, 1994)
This article revolves atound certain presuppositions, themes, and thmries related to a selected number of westem writings on Islamic nxurgence in the m&m Arab world. In this regard, I purport to examine the following claims: 1) Islamic resurgence is a widespread traditional, cultural, and political phenomenon in modem Islam; 2) some westem (and even Muslim) studies of Islamic TesuTgence have touched only the surface and, therefore, their methodological orientation has been inadequak, 3) as a facet of modem Islam, Islamic resurgence has reinterpreted the Islamic tradition in a creative and unique way; and 4) although the major leaders of the Islamic movement have placed philosophy outside the pale of Islam, one is tempted to study Islamic resurgence as a philosophical expression of modem and contemporary Muslim Societies.’ In order to show the theoretical inadequacy of the writings on Islamic tevivalism, I would like to discuss four Fecently published studies: Emmanuel Sivan, Radical Islam: Medieval Theology and Modern Politic? W. Montgomery Watt, Islamic Fundamentalism and Moderniq; Leanard Binder, Islamic Liberalism: A Critique of Development Ideologied; and Ronald Nettler, Past Trials and Present Tiibulation. In Radical Islam, Sivan proposes the following two ideas: First, to have a better understanding of the thinking of modem Islamic resurgence, especially that of Sayyid Qutb," one has to study the influence exerted ...